250 Colombian cassava farmers and a processor gain access to digital dry-matter measurement for quality control and pricing criteria transparency - Tran, Thierry; Taborda, Alejandro (2025)
A portable digital scale and web-based tool enable precise on-site measurement of dry matter which could harmonize cassava pricing and quality control. The innovation enables farmers measure cassava dry matter, aligning their quality standards with their buyers’ processors needs. Adoption is growing in Colombia with international interest. A manufacturing partner continues to produce and sell the device, ensuring scalability and sustainability. By bridging the information gap, the tool enhances fairness, transparency, and efficiency in cassava trade and processing.